Breastfeeding and adherence to ARV treatment with mother-to-child transmission of HIV at Sosodoro Djatikoesoemo Hospital, Bojonegoro - Endah Sri Wulandari; Ayu Wiwaningtyas (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: The HIV can be transmitted from an HIV-infected mother to her child during pregnancy, childbirth, and while breastfeeding. HIV that occurs in children is acquired because of transmission from mothers who do not comply with anti-retroviral drugs or during breastfeeding. Prevention of mother-to-child transmission of HIV is an effort aimed at preventing mother-to-child transmission in an integrated and comprehensive manner with other programs related to HIV control.Objectives: The study aimed to determine the relationship between breastfeeding and adherence to ARV treatment with mother-to-child transmission of HIV at Sosodoro Djatikoesoemo Hospital, Bojonegoro.Methods: The variables in the study were the independent variables of breastfeeding and adherence to ARV treatment in mothers and the dependent variable of HIV status in children under five. This type of research used a correlational analysis with a cross sectional design, with a population of 25 mothers who had babies aged 0-6 months and a sample of 25 respondents. Non-probability sampling technique, total sampling with research instruments using a questionnaire, and statistical tests using the chi-square test.Results: The results showed the significance value of breastfeeding, namely p = 0.001, while the significance value of adherence to ARV treatment was p = 0.009. This means that in this study the most dominant influence on HIV status in toddlers is breastfeeding.Conclusions: This study can analyze efforts to address maternal problems with HIV status to increase awareness of mothers with HIV status to keep checking both during pregnancy and after delivery to minimize transmission to their toddlers